Masalah dan Cara Mengatasi Sistem Informasi Akuntansi Siklus Pengeluaran Kas di PT NR - Engelwati Gani (Bina Nusantara University, 2014)
A problem in accounting information systems of expenditure cash cycle in PT NR is estimated purchase raw materials often left over and valuable. To overcome it, accounting information with computer-based systems was designed related to raw material purchase that is expected to speed up procurement process and avoid fraud and error. The system processes waste materials that will be stored and used properly, so as to increase efficiency in purchasing raw materials. The analysis used for the construction of this system was business process analysis, problem identification, and analysis of information needs. The result achieved is accounting information systems of expenditure cash cycle to overcome the problem existing in the company. Research concludes the use of information systems can speed up purchase process and avoid fraud. Raw material management with system will make it easier to perform the calculation of actual costs and improve internal control.